Non-permanent english teachers’ resilience in constructing professional identity in the remote areas of South Sulawesi - Upa, Yunika; Mbato, Concilianus Laos (COUNS-EDU: The International Journal of Counseling and Education, 2020)
Being a non-permanent English teacher in a remote area is not easy. The non-permanent teachers have to face many challenges. Without having resilience, the teachers can not survive to teach in the area. This study investigated the factors that influenced the resilience of the non-permanent English teachers in building a professional identity in the remote areas of South Sulawesi. The mixed-method explanatory sequential experimental design was used by involving non-permanent English teachers at five schools in the remote area of Tana Toraja, South Sulawesi Province. The RSA Scale questionnaire and interview were used to find out what factors influenced teachers’ resilience. The results showed that the challenges faced by non-permanent English teachers made them resilient teachers. Personal resources and contextual resources seemed to play a major role in their growth of resilience. The high resilience of teachers shapes their professional identity, which makes them stay afloat and think that teaching is their calling. This study suggests implications for the education of policymakers and the government in Indonesia, and also for future researchers who are interested in a similar topic may conduct further studies with a broader context